ROR1-targeting switchable CAR-T cells for cancer therapy - Peng, Haiyong; Nerreter, Thomas; Mestermann, Katrin; Wachter, Jakob; Chang, Jing; Hudecek, Michael; Rader, Christoph (Oncogene, 2022)
The success of chimeric antigen receptor T cell (CAR-T) therapy in the treatment of hematologic malignancies has prompted the development of numerous CAR-T technologies, including switchable CAR-T (sCAR-T) systems that combine a universal CAR-T with bispecific adapter proteins. Owing to their controllability and versatility, sCAR-Ts have received considerable attention. To explore the therapeutic utility of sCAR-Ts targeting the receptor tyrosine kinase ROR1, which is expressed in hematologic and solid malignancies, and to identify bispecific adaptor proteins that efficiently mediate universal CAR-T engagement, a panel of switches based on ROR1-targeting Fabs with different epitopes and affinities was compared in in vitro and in vivo models of ROR1-expressing cancers. For switches targeting overlapping or identical epitopes, potency correlated with affinity. Surprisingly, however, we identified a switch targeting a unique epitope with low affinity but mediating potent and selective antitumor activity in vitro and in vivo. Converted to a conventional CAR-T, the same anti-ROR1 mAb (324) outperformed a clinically investigated conventional CAR-T that is based on an anti-ROR1 mAb (R12) with 200-fold higher affinity. Thus, demonstrating therapeutic utility on their own, sCAR-Ts also facilitate higher throughput screening for the identification of conventional CAR-T candidates for preclinical and clinical studies.
CRIS-Team Scopus Importer:2023-03-23